Post-discharge prognosis of patients admitted to hospital for heart failure by world region, and national level of income and income disparity (REPORT-HF): a cohort study. Issue 3 (March 2020) - Tromp, Jasper; Bamadhaj, Sahiddah; Cleland, John G F; Angermann, Christiane E; Dahlstrom, Ulf; Ouwerkerk, Wouter; Tay, Wan Ting; Dickstein, Kenneth; Ertl, Georg; Hassanein, Mahmoud; Perrone, Sergio V; Ghadanfar, Mathieu; et al.
Summary: Background: Heart failure is a global public health problem, affecting a large number of individuals from low-income and middle-income countries. REPORT-HF is, to our knowledge, the first prospective global registry collecting information on patient characteristics, management, and prognosis of acute heart failure using a single protocol. The aim of this study was to investigate differences in 1-year post-discharge mortality according to region, country income, and income inequality. Methods: Patients were enrolled during hospitalisation for acute heart failure from 358 centres in 44 countries on six continents. We stratified countries according to a modified WHO regional classification (Latin America, North America, western Europe, eastern Europe, eastern Mediterranean and Africa, southeast Asia, and western Pacific), country income (low, middle, high) and income inequality (according to tertiles of Gini index). Risk factors were identified on the basis of expert opinion and knowledge of the literature. Findings: Of 18 102 patients discharged, 3461 (20%) died within 1 year. Important predictors of 1-year mortality were old age, anaemia, chronic kidney disease, presence of valvular heart disease, left ventricular ejection fraction phenotype (heart failure with reduced ejection fraction [HFrEF] vs preserved ejection fraction [HFpEF]), and being on guideline-directed medical treatment (GDMT) at discharge (p<0·0001 for all). Patients from eastern Europe had the lowest 1-year mortality (16%) and patients from eastern Mediterranean and Africa (22%) and Latin America (22%) the highest. Patients from lower-income countries (ie, ≤US$3955 per capita; hazard ratio 1·58, 95% CI 1·41–1·77), or with greater income inequality (ie, from the highest Gini tertile; 1·25, 1·13–1·38) had a higher 1-year mortality compared with patients from regions with higher income (ie, >$12 235 per capita) or lower income inequality (ie, from the lowest Gini tertile). Compared with patients with HFrEF, patients with HFpEF had a lower 1-year mortality with little variation by income level (pinteraction for HFrEF vs HFpEF <0·0001). Interpretation: Acute heart failure is associated with a high post-discharge mortality, particularly in patients with HFrEF from low-income regions with high income inequality. Regional differences exist in the proportion of eligible patients discharged on GDMT, which was strongly associated with mortality and might reflect lack of access to post-discharge care and prescribing of GDMT. Funding: Novartis Pharma.